2008
DOI: 10.1002/mrm.21537
|View full text |Cite
|
Sign up to set email alerts
|

Fat suppression for 1H MRSI at 7T using spectrally selective adiabatic inversion recovery

Abstract: Proton magnetic resonance spectroscopic imaging ( 1 H MRSI) at 7T offers many advantages, including increased SNR and spectral resolution. However, technical difficulties associated with operating at high fields, such as increased B 1 and B 0 inhomogeneity, severe chemical shift localization error, and converging T 1 values, make the suppression of the broad lipid peaks which can obscure targeted metabolite signals, particularly challenging. Conventional short tau inversion recovery can successfully suppress f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…We then used this data to normalize the amplitude of the required drive voltage and relative phase determined from the B 1 optimization in each of the 5 subjects. In this group (Fig 5) the coils directly under the posterior portion of the head (coils 1 and 2) show greater efficiency (lower required drive voltage) than the coils over the lateral (3, 4, 7, 8) and anterior portions of the brain (5, 6). This reflects the closer proximity of the back of the head to coils #1 and #2 than other brain regions to their nearest coils.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We then used this data to normalize the amplitude of the required drive voltage and relative phase determined from the B 1 optimization in each of the 5 subjects. In this group (Fig 5) the coils directly under the posterior portion of the head (coils 1 and 2) show greater efficiency (lower required drive voltage) than the coils over the lateral (3, 4, 7, 8) and anterior portions of the brain (5, 6). This reflects the closer proximity of the back of the head to coils #1 and #2 than other brain regions to their nearest coils.…”
Section: Resultsmentioning
confidence: 91%
“…Although adiabatic refocusing pulses can compensate for B 1 inhomogeneity, due to the limited B 1 they are also lengthy and deposit substantial amounts of RF power, making short echo times difficult to achieve. Thus to date the majority of spectroscopic imaging studies reported at 7T using volume head coils have used long echo times (5-7) making measurements of glutamate and glutamine difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Signals originating from these off-resonance regions such as subcutaneous lipids can cause baseline distortions in a large spectral range and hamper detection of the resonances of interest. However, by minimizing the global off-resonance effects by B 0 shimming, artifacts can be suppressed by low power frequency selective sequences (10). In this case OVS and slice selective refocusing may be omitted to reduce echo time and repetition time and therefore maximize SNR per unit time.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, fat signal can be removed by subtraction, but patient motion often limits the effectiveness of this approach. Fat suppression can be realized either by spectral‐selective saturation techniques, such as conventional or quick fat‐sat (QFS, where fat suppression radiofrequency [RF] pulses are applied once every several TRs), spectrally selective adiabatic inversion recovery (SPAIR) (21) technique, or by spectral‐selective excitation techniques with composite pulses (22, 23). Those techniques that rely on spectral‐selective RF pulses are sensitive to any B0 inhomogeneity and may therefore result in nonuniform fat suppression, especially in the vicinity of tissue interfaces and at higher field strength such as 3T.…”
mentioning
confidence: 99%